Clinical Phenotypes of Fontan Failure: Implications for Management. (26th May 2016) - Book, Wendy M.; Gerardin, Jennifer; Saraf, Anita; Marie Valente, Anne; Rodriguez, Fred
ABSTRACT: Fontan failure has been variably and inconsistently described in the literature, leading to challenges in comparing studies and evaluating treatments. Development of a conceptual framework to describe clinical phenotypes will aid in consistent terminology in the literature. In the heart failure literature, several key concepts have been described—"heart failure" is a clinical syndrome of various etiologies, with phenotype‐specific response to therapies. As the congenital heart disease community struggles to grapple with "Fontan failure, " these concepts come to light. Fontan failure in the context of four clinical phenotypes, including evaluation, potential management strategies, and future directions is discussed.